2015
DOI: 10.1016/s0140-6736(15)61485-4
|View full text |Cite
|
Sign up to set email alerts
|

Postural modification to the standard Valsalva manoeuvre for emergency treatment of supraventricular tachycardias (REVERT): a randomised controlled trial

Abstract: National Institute for Health Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
1
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(122 citation statements)
references
References 15 publications
1
107
1
13
Order By: Relevance
“…pressure of 40 mm Hg sustained for 15 s by forced expiration measured by aneroid manometer with the target pressure visible to the treating team). 1 The modified treatment was found to terminate SVTs in a significantly larger proportion of patients (43% of 214) than using conventional manoeuvres (17% of 214; P < 0.0001). As a consequence, significantly less patients in the study arm required adenosine (50% vs. 69%) or emergency anti-arrhythmic treatment (57% vs. 80%) to terminate the incident arrhythmia 1 and no differences in time to discharge from hospital.…”
Section: Cardiac Arrhythmias and Catheter Ablation Supraventricular Tmentioning
confidence: 86%
“…pressure of 40 mm Hg sustained for 15 s by forced expiration measured by aneroid manometer with the target pressure visible to the treating team). 1 The modified treatment was found to terminate SVTs in a significantly larger proportion of patients (43% of 214) than using conventional manoeuvres (17% of 214; P < 0.0001). As a consequence, significantly less patients in the study arm required adenosine (50% vs. 69%) or emergency anti-arrhythmic treatment (57% vs. 80%) to terminate the incident arrhythmia 1 and no differences in time to discharge from hospital.…”
Section: Cardiac Arrhythmias and Catheter Ablation Supraventricular Tmentioning
confidence: 86%
“…A recent postural modification to the traditional Valsalva manoeuvre has been published with some conversion success. (41) The initial phase is performed with the patient sitting in a semirecumbent position, followed by laying the patient supine and passively elevating the patient's legs once the strain is released. This augments the venous return to the heart and accentuates the surge in cardiac output, thus triggering a more effective vagal response.…”
Section: Valsalva Manoeuvrementioning
confidence: 99%
“…16 An updated Cochrane review of the effectiveness of the Valsalva manoeuvre found a reversion rate varying from 19.4% to 54.3%. 17 Recently, Appelboam and colleagues 18 compared the standard Valsalva manoeuvre with a modified one consisting of performing the manoeuvre in the same semi-recumbent position but, immediately after the Valsalva strain, having patients lie flat and raising their legs to 45° for 15 seconds. The modified manoeuvre was found to be significantly more effective in terminating the SVT (43% v. 17%).…”
Section: Nonpharmacologic Measuresmentioning
confidence: 99%